Design of embedded robust control systems using MATLAB®/Simulink® - Petkov, P. Hr. 1948-; Slavov, Tsonyo N.; Kralev, Jordan K. (IET control, robotics and sensors series ;, 2018)
The aim of this book is to give the necessary knowledge about the implementation of MATLABʼ and Simulinkʼ in the development of embedded control systems. Together, MATLAB and Simulink present a sophisticated programming environment which may be used for the design as well as for the implementation of embedded control systems. In this book, the authors exploit the opportunity to generate automatically and embed control code from Simulink models which allows to develop quickly efficient and error free code. The automated code generation and the availability of powerful processors make possible the implementation of complex high-order controllers which achieve fast and high-performance closed-loop dynamics.